Purwarupa Sistem Kendali Suhu Ruangan Kelas Universitas Pamulang Berbasis PLC Mitsubishi FX3U-24MR - Utomo, Luki; Marfin, Marfin; Setiawan, Dedi (Universitas Pamulang, Prodi teknik Elektro, 2024)
Every room at Pamulang University, Viktor Campus, Building B already uses air conditioning in the form of Air Conditioning (AC). AC is a device that requires a lot of power. The savings related to the use of AC are the background for this research with the implementation of a Pamulang University classroom temperature control system based on the Mitsubishi FX3U-24MR PLC. The use of photo sensors and temperature sensors in this system allows automatic control of the AC based on the presence of people in the room, temperature control outside the AC device is used as a comparison so that classroom conditions can remain comfortable. The aim is to optimize the use of AC and reduce efficient energy consumption. The design of this tool uses GXWorks2 software as a ladder diagram programming tool for the Mitsubishi FX3U PLC and Satool as a programming tool for creating data displays on the Samkoon HMI. The tool work system is equipped with Running Hours to monitor the working time of the AC device so that scheduling can be done from Monday to Saturday. Working time requirements are determined where Monday to Friday will be on (ON) at 07.00 am and will be off (OFF) at 09.40 pm, while Saturday will be on (ON) at 07.00 am and will be off (OFF) at at 06.20 pm. Calculation of AC power consumption under normal conditions is IDR. 79,875 per day and the estimated calculation of AC power consumption using a temperature control system is Rp. 55,468 per day, by using the Pamulang University classroom temperature control system based on the Mitsubishi FX3U-24MR PLC you can save usage costs of IDR. 24,406,272 per day.